اتهام ومحاكمة رئيس وأعضاء السلطة التنفيذية - شريف, ميثم حنظل; عبد الله, انتصار حسن (Journal of Legal Sciences, 2019)
When constitution basis decide that people is the source of decision and also the source of power, so must make a differ between the unique power of people and its practice from government that must makes that practice through a constitution and law framework, or accusing of not have law borders.As the accusation is an execution include constitution action, so must constitutions have a separate power act to make accusation direction for the president and execution power members which is the parliament because they represents people having a power to decide if one of the execution members has done an abuse act against the government, so legislations must put a special law for judging them, and these judgment's will be absolutely different from all other judgments which done by legislative power alone or by participating by both legislative and judgment powers.